Chemical Fingerprinting, Antioxidant, and Anti-Inflammatory Potential of Hydroethanolic Extract of Trigonella foenum-graecum - Hina Fatima; Muhammad Shahid; Chris Pruitt; Meredith A. Pung; Paul J. Mills; Muhammad Riaz; Rizwan Ashraf (MDPI AG, 2022)
In the current study, the antioxidant and anti-inflammatory potential of hydroethanolic extract of T. foenum-graecum seeds was evaluated. Phenolic profiling of T. foenum-graecum was conducted through high-performance liquid chromatography-photodiode array (HPLC-PDA) as well as through the mass spectrometry technique to characterize compounds responsible for bioactivity, which confirmed almost 18 compounds, 13 of which were quantified through a chromatographic assay. In vitro antioxidant analysis of the extract exhibited substantial antioxidant activities with the lowest IC50 value of both DPPH (2,2-diphenyl-1-picrylhydrazyl) and ABTS (2,2'-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid) inhibition assays. The extract was found to be non-toxic against human RBCs and murine macrophage RAW 264.7 cells. Moreover, the extract significantly (p < 0.001) reduced the lipopolysaccharide (LPS)-induced tumor necrosis factor alpha (TNF-α), intrlukin-6 (IL-6), prostaglandin E2 (PGE2), and nitric oxide (NO) in RAW 264.7 cells in a concentration-dependent manner. The hydroethanolic extract of T. foenum-graecum exhibited considerable anti-inflammatory potential by decreasing the cellular infiltration to the inflammatory site in both carrageenan-induced peritonitis and an air pouch model of inflammation. Pretreatment with T. foenum-graecum extract caused significant improvement in antioxidants such as superoxide dismutase (SOD), CAT (catalase), malondialdehyde (MDA), and myeloperoxidase (MPO) against oxidative stress induced by carrageenan. Based on our results of in vivo and in vitro experimentation, we concluded that hydroethanolic extract of T. foenum-graecum is a potential source of phenolic compounds with antioxidant and anti-inflammatory potential.